UPAYA PENCEGAHAN STUNTING PADA IBU HAMIL SERTA PENDIDIKAN KESEHATAN KADER DI PUSKESMAS MINAS - Jojor Sihotang; Febriani Febriani; Ninda Frymonalitza; Fania Pancar Fadilla; Sofi Sumarlin (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
In Indonesia, addressing malnutrition, especially stunting, has become urgency. The Indonesian Child Nutrition Status Survey (SSGBI) in 2019 highlighted a surge in stunting prevalence to 27.67%. Siak Regency witnessed a concerning rise in stunting cases from 19% in 2021 to 22% in 2022. This project aims to tackle these issues through anemia screening and evaluating the nutritional status of pregnant women at Puskesmas Minas. Puskesmas Minas employs Anemia Screening to identify cases with Hb levels below 11 g/dl, a crucial indicator of pregnancy-related anemia. The method involves anemia screening by assessing Hemoglobin levels and nutritional assessment based on pre-pregnancy eating habits, Upper Arm Circumference (LILA) measurements, Hemoglobin tests, and ultrasound examinations. The method for implementing this study activity is in the form of discussions with cadres and then providing education regarding stunting to cadres. 1 case was found that required further treatment at an advanced health facility. It can be concluded that there is a significant difference in cadres' knowledge before and after education about anemia and nutritional screening for pregnant women.